Supply Restrictions, Subprime Lending and Regional US House Prices - André Kallåk Anundsen; Christian Heebøll (Center for Economic Studies and ifo Institute (CESifo), 2015)
With regard to the recent US house price cycle, we analyze how the interaction between housing supply restrictions, mortgage credit constraints and a price-to-price feedback loop affects house price volatility. Considering 247 Metropolitan Statistical Areas, we estimate a simultaneous boom-bust system for house prices, housing supply and subprime lending. The model accounts for regional differences in supply elasticities that are determined by local variations in topographical and regulatory supply restrictions. Our results suggest that tighter supply restrictions lead to both a larger house price boom and bust, and that this is due to supply restricted areas being significantly more exposed to a financial accelerator effect and a price-to-price expectation mechanism. We further find that the presence of endogenous price ac-celeration mechanisms contribute to dilute the positive relationship between the total quantity response and the supply elasticity during a housing boom.
Keywords: G21; R14; R21; R31; 330; regional boom-bust cycles; housing supply restrictions; subprime lending; financial accelerator